Land-travel and sea-faring - Roberts, Morley, 1857-1942.; McCormick, A. D. (Arthur David), 1860-1943. (London : Lawrence and Bullen, 1891)
p. 177 Aboriginal man near Willandra Lakes asks for tobacco; p. 182-183 Aboriginal camps at sheep station Mossgiel; Aboriginal women ask for sheeps' heads; Aboriginal boy "Moses" makes stock whip handles out of myall wood in return for money; Aboriginal people's use of liquor; author's opinion that sale of liquor to Aborigines should be forbidden; Author's negative opinion about Aboriginal women; belief that Aboriginal race is doomed.
Ferguson, J.A. Bibliography of Australia
Keywords: Roberts, Morley, -- 1857-1942.; Seafaring life -- Great Britain; Voyages and travels; Mossgiel (SW NSW SI55-05); Willandra Lakes (SW NSW SI54-08)